An Analysis of Mind in Pre-schoolers Through Social Constructivism - Sawaira Maula Dad; Muhammad Sohail (Dialogue Social Science Review (DSSR), 2025)
This study is based on Vygotsky’s constructivism theory. Vygotsky constructivism theory is about social interaction, the theory considers learning as a social and communicative process. The study aims to highlight the importance of social interaction and application of different techniques and strategies that help preschoolers during their learning. The scaffolding technique within Zone of Proximal Development (ZPD) helps in cognitive development of the child making the learning process more active. This study also highlights how social constructivism theory enhances the cognitive ability of a child and emphasizes that social factors enhance the cognitive ability of pre-school children. Case studies and systematic participant observations were employed in this study and this research is qualitative in nature. Vygotsky theory of social constructivism helps the students to enhance their cognitive abilities.